Global Warming E-Worksheet Integrated with PhET Interactive Simulations: It is Effective to Enhance Students’ Critical Thinking Skills? - Wahdah, Nurul; Fitria, Trisonia; Arifa, Muh Fajrin; Jumadi, Jumadi; Hasyim, Mutahharah (STKIP Singkawang, 2024)
The aims of this research is to determine the effectiveness of the global warming e-worksheet using Liveworksheet integrated with PhET interactive simulations to improve students’ critical thinking skills. The independent variable is the use of a global warming e-worksheet integrated with PhET interactive simulations, while the dependent variable is the critical thinking skill (analyze the facts, formulate the main problem, interpreting, and summarizing). This research used a pre-experimental type, with a one-group pretest-posttest research design. At SMAN 4 Yogyakarta, 70 students in the 10th grade participated in the cluster random sampling technique. Criteria for measuring critical thinking skills were objective questions. Then, using SPSS, descriptive statistics, n-gain tests, and one-way ANOVA were used to examine the results. Results showed that the students' critical thinking skills were significantly enhanced by the global warming e-worksheet integrated with PhET interactive simulations. This points out that using electronic physics learning materials and integrating technology has a positive effect on improving cognitive skills. Students learn content during the learning process, but they also gain a deeper understanding of the material by using simulations that are based on real-world problems and scientific principles to complete e-worksheets.